Re-examining psychology : critical perspectives and African insights - Holdstock, T. Len (Routledge, 2000)
Re-examining Psychology takes a critical look at some of the principles underlying the discipline and offers an insight into alternative psychological perspectives deriving from sub-Saharan Africa.